"What then?": poststructuralism, authorial intention and W. B. Yeats - McNamee, Brendan (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2005)
Using aspects Yeats' s life and work (poems, philosophy, publishing episodes) as a lens, and focusing on the question of authorial intention, this paper explores certain conflicts and interrelations between traditional and poststructuralist theories of both textual and literary criticism. It will seek to show how Yeats himself embodies and mirrors this conflict in his work, both textually and thematically, and how the most important aspect of this conflict, for Yeats and for literature in general, is that it remains unresolved. Contrasting the ideas of E.D. Hirsch with those of Jerome McGann on the textual side and with those of Stanley Pish on the theoretical side, the paper seeks to highlight some limitations of the poststructuralist position, and also to show how these two apparently disparate schools of thought, traditionalist and poststructuralist, can occasionally exhibit some surprising affinities. The paper is indebted to George Bornstein's textual work on Yeats in its argument.